Teaching thinking skills across mathematics and science curriculum: an investigation of teachers' perceptions, practices and constraints in selected Saudi government schools in Medina - Alhabib, Nema Awad (Institute of Education, International Islamic University Malaysia, 2011)
Teachers' perceptions, practices and constraints they may encounter have not been the main focus of educational reform as the curriculum developments have been taken place for a long period of time. In order to enhance our students' thinking skills and improve their achievements, teachers have to be our targets for development and training. In this study, a self-constructed questionnaire was employed to investigate teachers' perceptions, practices and constraints of teaching thinking skills across Science and Mathematics curriculum. Purposeful and stratified random sampling techniques were used for selecting the female teachers of pilot and regular primary and middle schools in Medina. The findings indicated that the teachers have positive perceptions and they practice teaching thinking skills across the curriculum. However, the learning and teaching environment is not supporting them adequately towards the teaching thinking skills. Some of these constraints that hinder the effective teaching of thinking skills are inadequate tools and equipments; books and resources, time allocation, training workshops, lack of collaboration among teachers and insufficient assessment trainings. Further studies are recommended to investigate more on teachers' practices on teaching thinking skills across the curriculum, to overcome the constraints, and to design appropriate training programmes for teaching thinking across the curriculum.